Susceptibility of canine chondrocytes and synoviocytes to antibiotic cytotoxicity in vitro. Issue 3 (19th February 2021) - Newman, Robert J.; Chow, Lyndah; Goodrich, Laurie R.; Lambrechts, Nicolaas E.; Dow, Steven W.; Pezzanite, Lynn M.
Abstract: Objective: To evaluate relative cytotoxicity of antibiotics to normal canine joint tissues in vitro. Study design: Experimental in vitro study. Sample population: Chondrocytes and synoviocytes (three dogs); cartilage explants (three dogs); six dogs total. Methods: Chondrocytes and synoviocytes from normal femoropatellar joints of three dogs were plated on 24‐well plates (50 000 cells/cm 2, triplicate, 48 hours) and exposed to antibiotics (ampicillin sulbactam, vancomycin, cefazolin, ceftazidime, amikacin, enrofloxacin; 0.39‐25 mg/mL, 24 hours). Viability was assessed by using trypan blue dye exclusion. Antibiotic concentrations at which 50% cell death occurred (half‐maximal inhibitory concentration) were determined to rank antibiotics for relative cytotoxicity. Occurrence of caspase‐3 expression after antibiotic exposure was assessed as an indication of apoptosis induction. Cartilage explants from three different dogs were minced and exposed to antibiotics (amikacin, ceftazidime, cefazolin, enrofloxacin; 5 mg/mL, 72 hours). Live/dead staining was performed, and fluorescence was visualized by using confocal microscopy. Percentage of live vs dead cells was quantitated. Results: Viability of chondrocytes and synoviocytes decreased with increasing antibiotic concentrations. Half‐maximal inhibitory concentrations were determined for synoviocytes (vancomycin 13.77, ampicillin sulbactam 3.07, amikacin 2.26, ceftazidime 1.62, cefazolin 1.48, enrofloxacin 1.25 mg/mL) and chondrocytes (vancomycin 8.65, ampicillin sulbactam 8.63, ceftazidime 3.16, amikacin 2.74, cefazolin 1.67, enrofloxacin 0.78 mg/mL). Caspase‐3 expression was upregulated, providing evidence that apoptotic pathways were active in cell death. Conclusion: Half‐maximal inhibitory concentration data provided evidence of lower toxicity of vancomycin and ampicillin sulbactam to joint tissues in vitro. Clinical significance: These results provide evidence to justify future in vitro work with osteoarthritic joint tissues and in vivo clinical trials to evaluate safety and efficacy of intra‐articular antibiotics to treat dogs with septic arthritis.